ANALISIS IMPLIKATUR KONVENSIONAL DAN TINDAK TUTUR ILOKUSI DALAM PIDATO PRESIDEN JOKO WIDODO DI HARI ANTIKORUPSI SEDUNIA: (ANALYSIS OF CONVENTIONAL IMPLICATURES AND ILLOCUTIONARY ACTS IN PRESIDENT JOKO WIDODO’S SPEECH ON WORLD ANTI-CORRUPTION DAY) - Nanik Handayani; Wa Mulianti (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
Abstract This research focuses on analyzing conventional implicature and illocutionary speech acts in President Joko Widodo’s speech on International Anti-Corruption Day. A qualitative descriptive approach is used in this study, involving textual analysis and theoretical approaches from concepts in pragmatics and discourse analysis. The research utilizes the theory of conventional implicature by Grice and illocutionary speech acts by Austin and Searle. Additionally, discourse analysis by van Dijk and the relevance theory by Sperber and Wilson are employed to enhance the understanding of the analyzed data. The findings of this research reveal the presence of 5 sentences containing conventional implicature. Furthermore, there are 4 types of illocutionary speech acts consisting of 4 representative sentences, 3 directive sentences, 2 commissive sentences, and 1 declarative sentence. This demonstrates the complexity and depth of the analysis conducted to understand President Joko Widodo’s speech in the context of International Anti-Corruption Day. Keywords: Conventional implicature, Illocutionary speech acts, Presidential speech